2004
DOI: 10.1359/jbmr.0301220
|View full text |Cite
|
Sign up to set email alerts
|

Adipogenic Differentiation of Human Adult Stem Cells From Bone Marrow Stroma (MSCs)

Abstract: We assayed gene expressions during adipogenesis of human MSCs. Microarray assays demonstrated time-dependent increases in expression of 67 genes, including 2 genes for transcription factors that were not previously shown to be expressed during adipogenesis.Introduction: Increased numbers of bone marrow adipocytes have been observed in patients with osteoporosis and aplastic anemia, but the pathological mechanisms remain unknown. Recently, microarray assays for mRNAs were used to follow adipogenic differentiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
231
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 270 publications
(249 citation statements)
references
References 41 publications
15
231
0
3
Order By: Relevance
“…Differentiation studies in 3T3-L1 cells have reported that the expression of mRNA for FABP4 is absent in undifferentiated cells, is detectable by day 3 of differentiation and then rapidly increases towards a steady state around day 8 (several 100-fold increase in gene expression), for up to 28 days. 20,22,27 Similar profiles of FABP4 gene expression have been observed during the differentiation of human marrow and adipose tissue stromal cells into adipocytes, 28,29 as well as during the differentiation of SGBS cells. 16 We specifically analysed the expression profile of FABP4 during the differentiation of SGBS cells to relate GIPR expression to a well-established molecular differentiation marker of adipogenesis.…”
Section: Discussionsupporting
confidence: 53%
“…Differentiation studies in 3T3-L1 cells have reported that the expression of mRNA for FABP4 is absent in undifferentiated cells, is detectable by day 3 of differentiation and then rapidly increases towards a steady state around day 8 (several 100-fold increase in gene expression), for up to 28 days. 20,22,27 Similar profiles of FABP4 gene expression have been observed during the differentiation of human marrow and adipose tissue stromal cells into adipocytes, 28,29 as well as during the differentiation of SGBS cells. 16 We specifically analysed the expression profile of FABP4 during the differentiation of SGBS cells to relate GIPR expression to a well-established molecular differentiation marker of adipogenesis.…”
Section: Discussionsupporting
confidence: 53%
“…Cells from passage 2 were seeded at densities of 10,000 cells/cm 2 . Upon reaching the appropriate subconfluent level, cells were incubated in adipogenic induction medium (complete culture medium supplemented with 100 nM dexamethasone, 0.5 mM isobutylmethylxanthine and 100 μM indomethacin (Sigma-Aldrich)) for 21 days, as previously reported [14]. To evaluate lipid vesicle formation, cells were fixed with 4% formaldehyde and stained with 0.3% Oil Red O for 20 min.…”
Section: In Vitro Differentiation and Histological Analysismentioning
confidence: 99%
“…Bone marrow mesenchymal stem cells (MSCs) are currently among the best characterized adult stem cells (Majumdar et al, 1998;Pittenger et al, 1999) isolated from various tissue sources such as fat, muscle, and bone (Jiang et al, 2002b;Sottile et al, 2002;Zuk et al, 2002). These cells are able to differentiate into bone, fat, cartilage, muscle tissue, and neurons (Mackay et al, 1998;Reyes et al, 2001;Sekiya et al, 2004;Woodbury et al, 2000) and were ultimately reported in almost all cell lineages (Jiang et al, 2002;Krause et al, 2001). For these reasons, the isolation and manipulation of adult stem cells represents a promising tool for understanding tissue development and regeneration, as well as for studying the engineered repair of tissues and organs (Orlic et al, 2001;Pittenger and Martin, 2004;Wakitani et al, 2002).…”
Section: Introductionmentioning
confidence: 99%